Civic Engagement in Procurement : A Review of Eight International Case Studies - World Bank (World Bank, Washington, DC, 2013)
Procurement monitoring is a relatively new field for civic engagement. This paper is a collection of eight selected cases studies which aim to provide examples of practices that have emerged globally in recent years. The objective is not to offer 'blueprints' or ready-made solutions to the challenge of civic monitoring, but rather to highlight some of the broader complexities underpinning the successful development of new approaches. The cases studies are designed to explore how different mechanisms of civic engagement are forged within specific social and political contexts, and, more importantly, how the nature of such engagement changes over time. In particular, the studies focus on understanding the driving forces behind the process as it evolved the impact of the intervention, and the potential for replication at greater scale. While each case study can be viewed as a 'standalone' example, it is also important to emphasize the value of the collection in terms of developing the discussion of common principles of civic engagement in procurement.